ANALISIS VARIASI NUKLEOTIDA DAERAH D-LOOP DNA MITOKONDRIA PADA SATU INDIVIDU SUKU BALI NORMAL - Ratnayani, Ketut; Wirajana, I Nengah; Laksmiwati, A. A. I. A. M. (Jurnal Kimia (Journal of Chemistry), 2012)
Human mitochondrial DNA (mtDNA) has higher polimorfism level than nucleous genom, especially in the D-Loop region, which is a non coding region and the most polymorfic region in the mitochondrial genom. The analysis of variation of nucleotide sequence of D-Loop region can be used to determine the individual or ethnic identity and also maternal familiar relationship. The research aims to determine nucleotide variant on Balinese individue, which can be used as data base in determination of mtDNA genetical profile of Balinese ethnic in a bigger scale. To achieve the aims of the research, way the nucleotide sequence of one normal Balinese individue using the epithelia cells in the saliva. The methods were :1) the isolation of sample mtDNA, 2) the amplification of the DLoop region of mtDNA by PCR, 3) sequencing and analysis of nucleotides sequence. The 0,4 kb fragment of the D-loop region mtDNA of the sample were successfully amplified, and sequenced of 402 pb. The research found 6 new variants or morfe different from Cambridge or Anderson sequence : variant 16223C®T, 16249T®C, 16259C®T, 16278C®T, 16316A®G, 16375C®A. The research also found the deletion of T nucleotide on position 16362.
Keywords: mitochondrial DNA, D-Loop,Varian, Norma